2020
DOI: 10.1037/tra0000678
|View full text |Cite
|
Sign up to set email alerts
|

The role of pets in managing uncertainty from COVID-19.

Abstract: In an effort to manage the uncertainty brought on by the COVID-19 pandemic, many people have turned to their social support networks. With limited access to in-person human social networks, many people are turning to pets for social support. Pets may be a complementary social support to supplement virtual human-to-human interaction. Clinical Impact StatementComplementary social support from pets may reduce uncertainty thus potentially decreasing the risk for development of posttraumatic stress symptoms. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…Thus, people may continue to feel a sense of disconnect and isolation, especially if they live by themselves. This study furthers the work of Nieforth and O’Haire [ 42 ], demonstrating how “People may turn to their pets as a source of contact comfort”, a fact that could be particularly important during the Covid-19 pandemic for individuals who are living alone or are physically isolated from loved ones (p. 246). The results of this qualitative study support the growing body of literature regarding the importance of people’s relationships with their dogs [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, people may continue to feel a sense of disconnect and isolation, especially if they live by themselves. This study furthers the work of Nieforth and O’Haire [ 42 ], demonstrating how “People may turn to their pets as a source of contact comfort”, a fact that could be particularly important during the Covid-19 pandemic for individuals who are living alone or are physically isolated from loved ones (p. 246). The results of this qualitative study support the growing body of literature regarding the importance of people’s relationships with their dogs [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with previous research regarding the human and animal bond [ 23 , 24 ], dogs were seen as a support for mental health, as their canine companions offered not only a sense of connection, but also structure and routine. Nieforth and O’Haire [ 42 ] note that “individuals may perceive that their pets help to manage their uncertainty because caring for the pet remains a consistent routine in a time in which not much else is consistent or predictable.” (p. 246). For the most part, participants reported that their dog was an intrinsic part of their family, and they could not imagine their lives without them.…”
Section: Discussionmentioning
confidence: 99%
“…While the psychological consequences of COVID-19 are relevant across the lifespan, there Animals 2021, 11, 885 2 of 13 is significant risk to child and adolescent mental health in particular [2]. With a lack of in-person human-to-human social interaction due to social distancing, it is important to explore the role of relationships with companion animals in providing social support and buffering loneliness [4]. As more research emerges assessing human-pet relationships during the pandemic, there is a need for examining these relationships specifically in the context of adolescent loneliness and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Acquiring a dog has been associated with reduced loneliness [12,13], and there is some initial evidence that adolescents who own pets are less lonely than non-pet owners [14]. When access to face-to-face human social support is restricted due to the pandemic, pet owners may rely on their pets to supplement these interactions [4] and to diminish social isolation [15]. However, these findings are complex; for example, Powell et al [13] found that adjusting for covariates such as education level nullified the effects of dog acquisition on loneliness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation